Cutaneous Tumors in Swiss Dogs: Retrospective Data From the Swiss Canine Cancer Registry, 2008–2013. Issue 6 (November 2018) - Graf, Ramona; Pospischil, Andreas; Guscetti, Franco; Meier, Daniela; Welle, Monika; Dettwiler, Martina
Data collected in animal cancer registries comprise extensive and valuable information, even more so when evaluated in context with precise population data. The authors evaluated 11 740 canine skin tumors collected in the Swiss Canine Cancer Registry from 2008–2013, considering data on breed, sex, age, and anatomic locations. Their incidence rate (IR) per 100 000 dogs/year in the Swiss dog population was calculated based on data from the official and mandatory Swiss dog registration database ANIS. The most common tumor types were mast cell tumors (16.35%; IR, 60.3), lipomas (12.47%; IR, 46.0), hair follicle tumors (12.34%; IR, 45.5), histiocytomas (12.10%; IR, 44.6), soft tissue sarcomas (10.86%; IR, 40.1), and melanocytic tumors (8.63%; IR, 31.8) with >1000 tumors per type. The average IR of all tumor types across the 227 registered breeds was 372.2. The highest tumor incidence was found in the Giant Schnauzer (IR, 1616.3), the Standard Schnauzer (IR, 1545.4), the Magyar Vizsla (IR, 1534.6), the Rhodesian Ridgeback (IR, 1445.0), the Nova Scotia Duck Tolling Retriever (IR, 1351.7), and the Boxer (IR, 1350.0). Mixed-breed dogs (IR, 979.4) had an increased IR compared to the average of all breeds. Previously reported breed predispositions for most tumor types were confirmed. Nevertheless, the data also showed an increased IR for mast cell tumors and melanocytic tumors in the Nova Scotia Duck Tolling Retriever and for histiocytomas in the Flat Coated Retriever. The results from this study can be taken into consideration when selecting purebred dogs for breeding to improve a breed's health.